Structure of the male copulatory apparatus in Prognathorhynchus busheki (Platyhelminthes, Kalyptorhynchia). Issue 2 (20th May 2016) - Doe, David A.; Smith, Julian P.S.
Abstract: Gnathorhynchidae is a diverse taxon of predatory eukalyptorhynch flatworms characterized by an armed proboscis. Their present taxonomy is not concordant with what we know of their phylogeny. Further progress in this area is hindered by a lack of information concerning their morphology. As recent studies have shown, a historical reliance on live observations for species descriptions has resulted in a number of errors and omissions. Here, we redescribe the anatomy of the male copulatory organ of Prognathorhynchus busheki using transmission electron and confocal microscopy, correcting several errors in the original description. Furthermore, we use these results to update our understanding of the anatomy and evolution of male copulatory organs in Gnathorhynchidae and in Platyhelminthes more generally.